INSTAGRAM-BASED FINTECH MARKETING COMMUNICATION STRATEGY OF LIVIN’ BY MANDIRI - Rakhma, Meyla Tazqiya; Putri, Siti Syifazalia Anjariska P (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2025)
The digitalization of banking services has become imperative in today’s interconnected world, with mobile banking emerging as a key channel for financial transactions. This study aims to analyze the digital marketing communication strategy of Livin’ by Mandiri, the flagship mobile banking application of Bank Mandiri, through the lens of the SOSTAC framework comprising Situation, Objectives, Strategy, Tactics, Action, and Control and supported by SWOT analysis. A qualitative descriptive method was employed, involving document analysis, observation of Instagram marketing content, and secondary data review from official publications and user feedback. The research investigates how Bank Mandiri utilizes Instagram to engage digital-native consumers, promote its financial services, and position Livin’ by Mandiri as a lifestyle-driven financial platform. Findings reveal that Bank Mandiri integrates lifestyle marketing, financial literacy campaigns, and targeted promotions to build stronger customer relationships and encourage app adoption. Additionally, social responsibility initiatives further enhance brand credibility. However, usability and reliability issues remain key concerns based on recent user sentiment. This study concludes that a strategic, data-driven digital communication approach is essential to remain competitive in the fintech ecosystem. Future research should consider incorporating user interviews and comparative analysis across platforms to gain deeper insight into user experience and engagement.